2011
DOI: 10.3201/eid1708.101914
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009-associated Deaths Detected by Unexplained Death and Medical Examiner Surveillance

Abstract: During the pandemic (H1N1) 2009 outbreak, Minnesota, New Mexico, and Oregon used several surveillance methods to detect associated deaths. Surveillance using unexplained death and medical examiner data allowed for detection of 34 (18%) pandemic (H1N1) 2009–associated deaths that were not detected by hospital-based surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…We found that the majority of influenza A(H1N1)pdm09-associated pneumonia deaths in Thailand occurred in adults aged 20 to 60 years, which is similar to previous studies [16], [17], but differed from the older age predominance of seasonal influenza deaths [18], [19]. Only 53% of fatal cases with medical records reviewed had evidence of high-risk conditions for severe influenza infection, although the proportion was higher (67%) among all 198 fatal cases reported to NAIS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that the majority of influenza A(H1N1)pdm09-associated pneumonia deaths in Thailand occurred in adults aged 20 to 60 years, which is similar to previous studies [16], [17], but differed from the older age predominance of seasonal influenza deaths [18], [19]. Only 53% of fatal cases with medical records reviewed had evidence of high-risk conditions for severe influenza infection, although the proportion was higher (67%) among all 198 fatal cases reported to NAIS.…”
Section: Discussionsupporting
confidence: 88%
“…Although 198 hospitalized influenza A(H1N1)pdm09-associated pneumonia fatalities were identified, medical records were only available for review for 90 (45%). Additionally, some influenza A(H1N1)pdm09 deaths likely occurred outside of the hospital [34]. Therefore, our findings may not be representative of all hospitalized influenza A(H1N1)pdm09 pneumonia deaths or of fatal influenza A(H1N1)pdm09 cases in Thailand overall.…”
Section: Discussionmentioning
confidence: 85%
“…1 The identification of influenza ribonucleic acid in endomyocardial biopsies suggests that myocarditis (including fulminant cardiomyopathy) complicating influenza is caused by disseminated influenza infection. 2 The finding that influenza RNA has been identified in the myocardium in cases of sudden death, 2 and a recent study reporting that 15.4% of deaths due to pH1N1 in the United States occurred at home, 3 suggest that influenza infection may trigger arrhythmias and cardiac arrest. However, the incidence of myocardial involvement in influenza is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these individuals were younger and healthier than those found through active surveillance among hospitalized patients with influenza. UNEX/MED-X cases were more likely to have an autopsy done and were more likely to have died in their residences [18].…”
Section: Analysis and Dissemination Of Datamentioning
confidence: 99%